Adaptive Leadership in the Dynamics of Business in the Digital Era - Hasanah, Uswatul; Rozi, Fakhrur (International Journal of Public Administration and Policy, 2025)
In the digital era, characterized by rapid and unpredictable changes, adaptive leadership has become crucial for organizational sustainability. This study aims to examine the importance of adaptive leadership in facing business dynamics, the key characteristics required of adaptive leaders, implementation strategies, and the challenges involved. A descriptive qualitative method was used through a literature review approach. The results indicate that adaptive leaders must possess a clear vision, flexibility, strong communication skills, and the courage to make decisions amid uncertainty. Key strategies include training programs, encouraging innovation, and fostering team involvement. The main challenges are resistance to change and limited resources. In conclusion, adaptive leadership is not only a competitive advantage but also a necessity in addressing the challenges of the digital business landscape.